2017
DOI: 10.1186/s12977-017-0339-4
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal dynamics of HIV-1 transmission in France (1999–2014) and impact of targeted prevention strategies

Abstract: BackgroundCharacterizing HIV-1 transmission networks can be important in understanding the evolutionary patterns and geospatial spread of the epidemic. We reconstructed the broad molecular epidemiology of HIV from individuals with primary HIV-1 infection (PHI) enrolled in France in the ANRS PRIMO C06 cohort over 15 years.ResultsSociodemographic, geographic, clinical, biological and pol sequence data from 1356 patients were collected between 1999 and 2014. Network analysis was performed to infer genetic relatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
46
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 41 publications
(59 citation statements)
references
References 62 publications
(83 reference statements)
12
46
1
Order By: Relevance
“…A concomitant decrease of the number of PHI cases that involved subtype B strains was observed in 2014 and 2015. The steady increase between 2010 and 2013 of the proportion of non‐B subtypes among patients with PHI in Southeastern France is consistent with recent results from France and other European countries . As stated by Chaix et al, non‐B subtypes were present among patients with PHI diagnosed in all French regions, and their prevalence among PHI cases increased, reaching 28%.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…A concomitant decrease of the number of PHI cases that involved subtype B strains was observed in 2014 and 2015. The steady increase between 2010 and 2013 of the proportion of non‐B subtypes among patients with PHI in Southeastern France is consistent with recent results from France and other European countries . As stated by Chaix et al, non‐B subtypes were present among patients with PHI diagnosed in all French regions, and their prevalence among PHI cases increased, reaching 28%.…”
Section: Discussionsupporting
confidence: 87%
“…The emergence of clusters of CRF02_AG strains among MSM experiencing PHI was recently described in Southeastern France and later at the national scale . Overall, in France, the dynamics of the HIV epidemics in the MSM population indicates a recent and rapid dissemination of CRF02_AG strains through connected networks of MSM . In the present work, HIV‐1 variants and atypical recombinants forms were mostly found in the most recent period, in 2013‐2015.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…This offers the opportunity to intensify prevention and testing programmes in this area to eventually impact HIV transmission in this area, and possibly elsewhere in France. Indeed, recent phylogenetic studies concluded that the region Ile‐de‐France was the major hub of dissemination in France , and that among clusters of primary HIV infections involving patients living in not contiguous regions 70% involved one patient living in Paris area . This suggests that reducing HIV transmission in Ile‐de‐France could indirectly reduce HIV transmission in other regions of France.…”
Section: Discussionmentioning
confidence: 99%
“…However, one branch of the tree was overrepresented with 13 sequences from our panel. It has recently been shown that some of the subjects included in this study were part of an ongoing cluster of transmission, based on pol gene analysis (37), which was not known at the time of the panel generation. All individuals infected by these viruses were Caucasian MSM.…”
Section: Panel Of Crf02_ag Env Pseudotyped Viruses From Acute/early Hmentioning
confidence: 99%